2012
DOI: 10.1582/leukos.2012.09.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Automotive Interior Lighting on Driver Vision

Abstract: There has been growing interest in vehicle interior lighting for both functional and aesthetic purposes. Although there is a large body of research on nighttime driver vision and vehicle exterior lighting, there has been little research attention to vehicle interior lighting. This report includes a brief review of some of the research that has been done, and presents the results of a nighttime field study that was performed to contribute to the understanding of how vehicle interior lighting affects some basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Under nighttime conditions, a peak intensity of 200 cd resulted in asymptotic response times, and higher-intensity lights were not detected more quickly. In comparison, Flannagan et al (2008) reported that a peak intensity of 1000 to 2000 cd was necessary during daytime conditions when the warning beacon was located about 45 o from the line of sight. This peripheral angle was substantially larger than those studied by Rea and Bullough (2016), who used peripheral angles up to 5 o on the bases that the principal viewing angles for warning beacons were no larger than 5 o (Howard and Finch, 1960), and drivers’ gaze locations were rarely more than 5 o from the road ahead (Mourant and Rockwell, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Under nighttime conditions, a peak intensity of 200 cd resulted in asymptotic response times, and higher-intensity lights were not detected more quickly. In comparison, Flannagan et al (2008) reported that a peak intensity of 1000 to 2000 cd was necessary during daytime conditions when the warning beacon was located about 45 o from the line of sight. This peripheral angle was substantially larger than those studied by Rea and Bullough (2016), who used peripheral angles up to 5 o on the bases that the principal viewing angles for warning beacons were no larger than 5 o (Howard and Finch, 1960), and drivers’ gaze locations were rarely more than 5 o from the road ahead (Mourant and Rockwell, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, research on capsule hotel lighting by Yu et al explored illumination levels of 150 lx and 300 lx [20], while Chen et al investigated a range from 20 lx to 250 lx in very small spaces, finding optimal comfort at 100 lx before it declined with increased brightness [21]. These variations in research parameters and findings highlight the complexity of adapting lighting studies from conventional to specialized small spaces [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Michael Flannagan and his research team’s work are relevant to our study: Ref. [ 33 ] is in one of their earliest studies we are aware of relating to the role of vehicle adaptive lighting; the authors of [ 34 , 35 , 36 ] studied the precise role of light location, intensity and beam spread. Dawn Tilbury and her team have also made significant contributions to this topic: in [ 37 ], they measured the behavior of pedestrians at crosswalks using an immersive virtual environment and related it to the real world.…”
Section: Introductionmentioning
confidence: 99%